QORAQALPOG‘ISTON RESPUBLIKASI SHAROITIDA ZIZIPHUS JUJUBA MILL., O‘SIMLIGINING INTRODUKSIYASI - Azilova, U.T.; Ajiev, A.B. (SCIENCE and SOCIETY, 2024)
In the article, the goal and task of introducing Ziziphus jujuba Mill., to the Republic of Karakalpakstan, the economic importance of its cultivation, and the methods of cultivation in field conditions were analyzed. Many medicinal properties of unabi fruit have been mentioned.
Keywords: introduction; flora; anemia; pulp; choylon; asthma; smallpox; hypertension